Identification of a Locus Conferring Dominant Susceptibility to Pyrenophora tritici-repentis in Barley - Wei, Bohan; Moscou, Matthew J.; Sato, Kazuhiro; Gourlie, Ryan; Strelkov, Stephen; Aboukhaddour, Reem (Frontiers in Plant Science, 2020)
The fungus Pyrenophora tritici-repentis (Ptr) causes tan spot, a destructive foliar disease of wheat worldwide. The pathogen produces several necrotrophic effectors, which induce necrosis or chlorosis on susceptible wheat lines. Multiple races of Ptr have been identified, based on their ability to produce one or more of these effectors. Ptr has a wide host range of cereal and non-cereal grasses, but is known to cause damage only on wheat. Previously, we showed that Ptr can interact specifically with cultivated barley (Hordeum vulgare ssp. vulgare), and that the necrotrophic effector Ptr ToxB induces mild chlorosis in a highly selective manner when infiltrated into certain barley genotypes. In the present study, a barley doubled-haploid (DH) population was evaluated for reaction to Ptr race 5, a Ptr ToxB-producer. Then a comprehensive genetic map composed of 381 SNP markers was used to map the locus conditioning this chlorosis. The F1 seedlings, and 92 DH lines derived from a cross between the resistant Japanese malting barley cultivar Haruna Nijo and the susceptible wild barley (H. vulgare ssp. spontaneum) OUH602 were inoculated with a conidial suspension of Ptr race 5 isolate at the two-leaf stage. The seedlings were monitored daily for symptoms and assessed for chlorosis development on the second leaf, 6 days after inoculation. All tested F1 seedlings exhibited chlorosis symptoms similar to the susceptible parent, and the DH lines segregated 1:1 for susceptible:resistant phenotypes, indicating the involvement of a single locus. Marker-trait linkage analysis based on interval mapping identified a single locus on the distal region of the short arm of chromosome 2H. We designate this locus Susceptibility to Pyrenophora tritici-repentis1 (Spr1). The region encompassing this locus has 99 high confidence gene models, including membrane receptor-like kinases (RLKs), intracellular nucleotide-binding, leucine-rich repeat receptors (NLRs), and ankyrin-repeat proteins (ANKs). This shows the involvement of a dominant locus conferring susceptibility to Ptr in barley. Further work using high-resolution mapping and transgenic complementation will be required to identify the underlying gene.